Phytochemical Analysis and Assessment of Antibacterial Efficacy of Vernonia amygdalina (Bitter Leaf) against Some Selected Clinical Bacterial Isolates - Auwal Magaji; Zinat Mahmud; Aminu Mustafa (UMYU Journal of Microbiology Research)
Vernonia amygdalina is a plant known to contain substances with reported antimicrobial properties against various microorganisms. This study therefore, aimed at assessing the antibacterial properties of Vernonia amygdalina extract against some clinical bacterial isolates. The bacterial isolates were obtained from General hospital Azare, and the Vernonia amygdalina leaves were purchased at Azare central market. Various compounds, including saponins, glycosides, tannins, flavonoids, steroids, phenolic compounds, and alkaloids, were identified in the plant extract via phytochemical screening. Different concentrations of the V. amygdalina extract (25mg/mL, 50mg/mL, and 100mg/mL) were prepared and screened for antibacterial using disc diffusion method, revealing  zones of inhibition of 7.00 mm, 9.00 mm and 4.00 mm against Escherichia coli, Staphylococcus aureus, and Klebsiella pneumoniae respectively, at 100mg/ml of the extract. The MIC of the extract against Escherichia coli and Staphylococcus aureus was 25 mg/mL, whereas 50 mg/mL of the extract was found to be the minimum concentration active against Klebsiella pneumoniae. The study found that the extract exhibited modest antibacterial activity, with different minimum inhibitory concentrations for the bacterial strains.